PENERAPAN MEDIA VISUAL POP-UP BOOK DALAM MENINGKATKAN HASIL BELAJAR PADA PEMBELAJARAN IPS DI SEKOLAH DASAR - Maharani, Cantika; Yogiarni, Tiara; Mulyani, Srie (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The background of this research is due to the low learning outcomes of the students of the V grade of SD Negeri Kamojing I due to lack of use of learning media, so that the students are less active. The purpose of this study is to describe the application of the visual learning visual media pop-up book in learning and to find out the impact of the use of visual media pop-up book in improving the learning outcomes of Social Science in students of grade V in SD Negeri Kamojing I. The research method used in this research is class action research which consists of 2 cycles with measures including planning, implementation, observation, and reflection. Based on the results of the research, the application of the visual media pop-up book implemented using the cooperative learning model of the Student Teams Achievement Division (STAD) and the learning outcomes of students of grade V SD Negeri Kamojing I improved, in cycle I the average grade score was 66.4 and in the cycle II was 83.5. The improvement in learning outcome obtained in the Cycle II of the cycles I was 17.1. It shows that after given action using visual media pop-up book can improve the learning results of IPS students of grade V SD Negeri Kamojing I, Kecamatan Cikampek, Kabupaten Karawang.   Keywords: learning outcomes, pop-up book, social science, visual media